Derivação de um modelo de três modos para condensados de Bose-Eisntein a partir de uma proposta experimental - (:unkn) unknown (Universidade Federal do Pampa, 2018)
In this monography, based on an experimentally viable proposal, we derive a model for describing the behavior of a dipolar Bose-Einstein condensates confined in triple well non aligned potentials. The model takes into account interactions of short and long range, tunnelingbetween adjacent potential wells and an anisotropy associated to interwell dipoledipole interactions. Using analytical and numerical calculation, the classical and quantum dynamics for the expectation values of the populations in each well, are investigated. Then, by using perturbation theory tools, an effective Hamiltonian is deduced. Through a semiclassical approach, analytical results are presented. Lastly, we show that the modelwith three mode can simulate a device like-transistor.
Keywords: Condensado de Bose-Einstein; Atomotronica; Integrabilidade; Modelagem matemática; Bose-Einstein condensate; Atomtronics; Integrability; Mathematical modeling; CNPQ::CIENCIAS EXATAS E DA TERRA